2012
DOI: 10.1037/a0026536
|View full text |Cite
|
Sign up to set email alerts
|

Tactile perceptual processes and their relationship to somatoform disorders.

Abstract: The Somatic Signal Detection Task (SSDT) is a recent paradigm serving to examine perceptual processes likely relevant for somatoform disorders. We tested whether touch illusions are more easily induced in individuals suffering from somatoform disorders (SFD) and whether their perceptual threshold for tactile stimuli is lower compared to healthy controls. Thirty-three participants with SFD and 32 healthy controls reported whether they recognized near-threshold tactile stimuli at their fingertip, which were pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 53 publications
2
19
2
Order By: Relevance
“…Additionally, persistent TMD pain may heighten sensitivity to internal physical sensations and pain. A biological sensitivity to somatic feelings could predispose a person to developing somatisation . Other psychological factors, such as depression, anxiety or stress, may also be associated with pain intensity based on the previous literature, but the association was not direct, because pain was not their major symptom.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, persistent TMD pain may heighten sensitivity to internal physical sensations and pain. A biological sensitivity to somatic feelings could predispose a person to developing somatisation . Other psychological factors, such as depression, anxiety or stress, may also be associated with pain intensity based on the previous literature, but the association was not direct, because pain was not their major symptom.…”
Section: Discussionmentioning
confidence: 99%
“…Because the cerebral cortex controls sensory–motor coupling, sensory feedback system, and somatic sensation, cortical damage may cause increased sensitivity to internal physical sensations and pain. The increased sensitivity to somatic feelings may predispose patients to produce somatoform symptoms (105, 106). …”
Section: Correlation Between Clinical Manifestations and Histomorpholmentioning
confidence: 99%
“…Other studies investigating attentional processing of bodily sensations themselves provide some evidence for a relationship between attention to the body and symptom reporting, although also implicate avoidance of bodily sensations Brown et al, 2010). Interestingly, Katzer et al (2012) found that lower tactile perceptual thresholds were associated with fewer symptoms in patients with somatoform disorders on the Somatic Signal Detection Task (SSDT). Other studies found that both somatoform disorders (Katzer et al, 2012) and symptom reporting more generally (Brown et al, 2010Katzer et al, 2011) were associated with a tendency to report sensory experiences on the SSDT regardless of whether stimuli were actually presented (i.e.…”
Section: Interoceptive Hypervigilance Thresholds and Awarenessmentioning
confidence: 99%
“…Interestingly, Katzer et al (2012) found that lower tactile perceptual thresholds were associated with fewer symptoms in patients with somatoform disorders on the Somatic Signal Detection Task (SSDT). Other studies found that both somatoform disorders (Katzer et al, 2012) and symptom reporting more generally (Brown et al, 2010Katzer et al, 2011) were associated with a tendency to report sensory experiences on the SSDT regardless of whether stimuli were actually presented (i.e. 'false alarms'), seemingly contradicting the prediction of improved accuracy.…”
Section: Interoceptive Hypervigilance Thresholds and Awarenessmentioning
confidence: 99%